Locus coeruleus syndrome as a complication of tectal surgery. (22nd April 2015) - Kronenburg, Annick; Spliet, Wim G; Broekman, Marike; Robe, Pierre
Abstract : We describe a case of a 48-year-old woman who underwent a resection of a tectal pilocytic astrocytoma complicated by a sequence of fluctuating consciousness, psychosis with complex hallucinations and lasting sleeping disturbances in which she vividly acts out her dreams. Based on the clinical and anatomical evidence of this case, we propose the term locus coeruleus syndrome to describe this association of iatrogenic symptoms. Along with those of the locus coeruleus, lesions of the dorsal raphe nucleus, ventral tegmentum, substantia nigra pars compacta, the superior colliculus and other peduncular lesions (such as peduncular hallucinosis) are involved in the regulation of sleep-wake/arousal, behaviour, sleeping disorders and rapid eye movement atonia. However, iatrogenic lesion of the locus coeruleus could explain the complications on all levels in our patient.